The temporal variation in Siberian flying squirrel (Pteromys volans) population size - Koskimäki, Jane (2011)
Human land use causes declines of natural populations, for example, by loss of habitat area. Additionally, habitat fragmentation can cause the population size to decline more than is expected based on the area lost. Some ecological processes, such as demographic stochasticity and Allee effect, can expose already small populations to further decline. The endangered Siberian flying squirrel (Pteromys volans) has suffered from intensive forestry in Finland. In this thesis I estimated the size and growth rate of a local flying squirrel population living in nest boxes in Alavus using 15-year mark-recapture data. I regressed the estimated population size against habitat availability to detect relationships between the variables and also possible effects of fragmentation. The adult population size decreased from 65 to 29 in 1995–2009. The growth rate was less than one during the time period, also indicating a decline. The survival probability for adults was about 0.5 and for juveniles 0.22, both being constant in time and quite equal to another study in Finland. Population size declined with decreasing habitat area and the number of box sites, but no effect of fragmentation was seen, since the relationship between population size and habitat area was linear. There was also temporal variation in population size not caused by habitat availability but other reasons, for example demographic and environmental stochasticity or predator species. Therefore, the generalizability of single year census is not very good. Additionally, predicting the current or future population size only based on habitat availability is dangerous, which should be considered in the conservation of the flying squirrel populations. The availability of cavity and foraging trees is important for the persistence of the species. Maybe the conservation of the species also requires placing nest boxes to enable living in habitats of poor quality when preferred habitats are cut down. The nest boxes could have saved the population from extinction so far, but with similar forest cutting the population could go extinct in 15 years.